Effect of substitution of (NiNb)4+ into B-sites on the phase formation, microstructure and electrical properties of Bi0.47Na0.47Ba0.06TiO3 ceramics - Anupong Luangpangai; Pamornnarumol Bhupaijit; Nipaphat Charoenthai; Naratip Vittayakorn; Sarawut Thountom; Theerachai Bongkarn (Ferroelectrics, 2022)
Bi0.47Na0.47Ba0.06Ti1-x(Ni1/3Nb2/3)xO3 ceramics (abbreviated as BNBT1-x(NN)x, x = 0, 0.01, 0.03 and 0.05) were synthesized by solid-state combustion. The effect of x on the phase formation, microstructure and electrical properties of BNBT1-x(NN)x ceramics was examined. The XRD pattern indicated the coexistence of rhombohedral and tetragonal phases in all the specimens. Moreover, Rietveld refinement confirmed that the tetragonal phase increased from 47 to 71% when x increased from 0 to 0.05. The morphology of BNBT1-x(NN)x ceramics was observed by SEM and the ceramics grains showed polygonal shapes and the grain growth tended to be anisotropic. With (NiNb)4+ substitution, the average grain sized decreased rapidly from 1.7 to 1.0 µm and the grain size distribution was narrower as the amount of (NiNb)4+ increased. The density, remnant polarization (Pr) and coercive field (Ec) rapidly decreased with increasing x. A significant decrease in the ferroelectric properties was caused by the increasing tetragonal phase.
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Multiferroics and related materials